Pasig City cultural complex - Aguilar, Jerome R. (Manila : National University, 2000)
The general objective of the project is to establish a cultural complex in the city of Pasig located in Brgy. Ugong along Meralco Avenue to promote tourism in the city and improve educational, social, and cultural development as well as economic development of the city.